Morphological diversity of springtails in agroflorestais systems in the southwest of Paraná (Research, Society and Development, 2020)
Agroforestry systems promote sustainable production models, thus favoring the development of edaphic fauna. In this sense, the study aimed to evaluate the morphological diversity of colembola, in three agroforestry systems, one of which has already been consolidated with 8 years of implementation (SAF1) and two others in the process of establishing the agroforestry system with 3 years (SAF2 and SAF3). The soil fauna was sampled from the installation of 10 Pitfall-trap in each of the areas, which remained in the field for 7 days. After their removal, they were transferred to the laboratory and their contents were washed in a fine mesh sieve, and Collembola class individuals were classified into morphotypes. The data obtained were analyzed for abundance, group richness and for the diversity indices of Shannon and Pielou equitability. As a result, 29 morphotypes were obtained, the group of epigenetic organisms being the most expressive and the morphotype Epi4 the most representative among the areas. SAF1 presented greater abundance and richness of morphotypes, as well as greater values of diversity and uniformity, indicating that in the long term agroforestry systems favor the development of this group.